Un modello di comunità: il gruppo che cura il gruppo - Esposito, Gaia; Reggio D'Aci, Matteo; Tedesco, Canio; Zucchini, Roberto (Il sogno della farfalla, 2016)
This paper aims to briefly recount the noteworthy moments in the history and workings of a psychiatric community engaged in the psychotherapy of psychoses. After an initial period characterized by a pharmacological and assistive approach, the treatment changed radically thanks to the introduction of Massimo Fagioli’s Birth Theory. This practice, based on a theory, methodology, treatment/training of the therapists and a nonconscious relationship with the patient, has structured itself through a team of four therapists practising five days a week. The team’s coherence and constancy have rendered transference, interpretations and even the setting altogether special, to the point where the definition “the group that cures the group” has come into being whereby it is the group of therapists that cures the group of patients. During the week end, testing ground of the therapeutic week, patients can either fall into a crisis or organize their free time with creativity depending on whether the annulment drive or a memory-fantasy prevails at the moment of separating from the therapists.